Electronic Banking: Its Use and Challenge in Nepal - Shah, Krishna Kumar (Academic Voices: A Multidisciplinary Journal, 2016)
Electronic banking, new strategies have become necessary in order to attract and retain existing customers, changing business environments, globalization and the advancement of information and communication technology. Despite enormous pressures for change and investment in information technology in the banking field; if these investments do not work in accordance with the principles of investment, they will fail. The available sources and studies conducted in the field, seek to find out the main factors and challenges posed in the development of electronic banking after a relatively long period of adoption in Nepal. This paper highlights the challenges for the development of e-banking, its impact of infrastructural barriers, legal and security barriers and management-banking barriers on the development of e-banking in Nepal. Academic Voices Vol.5 2015: 9-15